Putting the broken pieces of life together, Baloch family caregivers’ confrontation with schizophrenia: a phenomenological study - Nastaran Heydarikhayat; Fatemeh Darban; Jamileh Farokhzadian (BMC Psychology)
Abstract Background Long-term care of patients with schizophrenia, which creates a burden of care, leads to disruption in interactions, social and personal relationships, changes in lifestyle, and shifts in the roles of family members. This study aimed to explore the lived experiences of family caregivers who are caring for a family member with schizophrenia within the Baloch ethnicity. Methods This is a qualitative study, using a descriptive phenomenological approach. A total of fifteen family caregivers of patients with schizophrenia participated in the study. Data were collected by a semi-structured interview. Results Twenty-one categories, seven sub-themes and one theme were extracted. “Putting the broken pieces of life together” was the main theme with sub-themes of “Ignorance confrontation”, “Schizophrenia acceptance process”, “Restoring a chaotic context with human and non-human approaches”, “Support seeking”, “Escaping from stigma”, “Roles restoring”, and “Lifelong caring”. Conclusions For a family with a member with schizophrenia, restoring family life is a top priority. However, schizophrenia is so debilitating and destructive that it threatens not only the peace of the family but also the survival of the family, and it requires constant effort and complete support to restore and maintain life.